PENGARUH MODEL TTW BERBANTU MEDIA EXPLOSION MAGIC BOX TERHADAP KEMAMPUAN BERPIKIR KREATIF - Gina Faojina; Agus Saeful Anwar; Yani Fitriyani; Oman Hadiana (Jurnal Lensa Pendas, 2024)
The aim of this research is to find out how the Think Talk Write (TTW) learning model combined with explosion magic box media influences the creative thinking abilities of class IV Science and Technology students at SD Negeri 1 Cigadung. This research uses Nonequivalent Control Group Design combined with Quasi Experimental Design techniques. The research subjects were students in class IVA and IVB at SD Negeri 1 Cigadung, consisting of 18 people in class IVA and 19 people in class IVB. To obtain information about students' creative thinking capacity, a pretest and posttest consisting of ten questions were used as a data collection approach. The research results show that the Think Talk Write (TTW) learning model and magic box explosion media have an impact on the creative thinking abilities of class IV students. The hypothesis finding Sig (2-tailed) 0.032 is less than 0.05. Therefore, H0 is rejected or H1 is approved, meaning that the creative thinking capacity of class IV Science and Technology students at SD Negeri 1 Cigadung is affected by the use of the Think Talk Write (TTW) model assisted by explosion magic box media.